Pengaruh Gaya Kepemimpinan Terhadap Kinerja Pegawai Pada Dinas Koperasi Perindustrian Dan Perdagangan Kota Bima - Nurlaili Nurlaili; Kartin Aprianti (Manajemen Kreatif Jurnal, 2023)
This research aims to determine the influence of leadership style on employee performance at the Bima City Industry and Trade Cooperative Service. The sample in this research was 40 ASN with a sampling technique, namely purposive sampling. The research method uses questionnaires, observation and interviews. The data analysis technique uses simple linear regression. The results of the research show that leadership style has a significant effect on employee performance at the Bima City Industrial and Trade Cooperative Service.